Renal vein thrombosis, light-chain deposition disease and cast nephropathy in a multiple myeloma patient - Vilma Takayasu; Silvana Maria Lovisolo; Leonardo de Abreu Testagrossa; Aloísio Felipe-Silva (University of São Paulo, 2011)
A 56-year-old woman presented with thoracic pain and dyspnea for 3 days. She had been under treatment for systemic arterial hypertension for 16 years. Laboratory investigation showed acute renal failure with indication for hemodialysis. After dialysis, despite improvements in clinical and laboratory parameters, she had an episode of ventricular fibrillation and cardiac arrest which was promptly reverted. She was still oliguric but without neurological deficits. A laboratory work up for multiple myeloma was started. Serum protein  electrophoresis showed hypogammaglobulinemia without a monoclonal peak. While on laboratory work up, the patient had another episode of ventricular fibrillation and died. The autopsy showed left renal vein thrombosis, bone marrow involvement by a plasmacytic myeloma, light-chain deposition disease with diffuse glomerular and tubular involvement and also myeloma cast nephropathy. This case illustrates a rarely documented association between myeloma cast nephropathy, renal light-chain deposition disease and renal vein thrombosis in a multiple myeloma patient with acute renal failure.